Mouvements de terrain et urbanisation le long du Criş Repede en amont de la ville d'Oradea (Roumanie) - Christelle Sosson; Alain Marre; Nicolae Josan (Physio-Géo)
A new residential district is under construction on the southern slope of Oradea Hills located in the eastern part of the town of Oradea and on right bank of the Cris Repede. The new houses are distributed according to two alignments: one on the top of the interfluve and the other, denser, at the bottom of the slope. Gardens and terrace cultivation can be found between these two developments. Therefore, this green slope in the vicinity of the urban center constitutes a place favourable for urban extension. Nevertheless, numerous landslides can be found on these slopes composed of late Tertiary detrital formations (sands, marls and sandstones) deposited by the Pannonic Sea. Several types of landslides were observed: rotational, muddy castings and side extensions locally known as "glimées". These landslides can be explained by the conjunction of favourable factors which can be permanent (topography, geology, hydrology) or occasional (precipitations). Chronological study made it possible to identify four generations of landslides. Signs such as cracks affecting walls or warped trees show that these movements are still active.